2022
DOI: 10.55075/wa.v46i1.98
|View full text |Cite
|
Sign up to set email alerts
|

Penentuan Isoterm dan Kinetika Adsorpsi Ion Besi oleh Sedimen Sebagai Adsorben

Abstract: Kemampuan adsorpsi ion besi oleh sedimen telah dikaji dalam pengaruh variasi konsentrasi ion besi dan waktu kontak untuk menentukan isoterm dan kinetika adsorpsi. Isoterm adsorpsi didasarkan pada hasil adsorpsi ion besi pada konsentrasi 10 sampai 30 ppm dengan interval 5 ppm. Lebih lanjut, kinetika adsorpsi ditentukan dari variasi waktu kontak yaitu 30 sampai 150 menit dengan interval 30 menit. Semua hasil adsorpsi ion besi oleh sedimen diukur dengan menggunakan spektrofotometer serapan atom. Hasil penelitian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Based on the R 2 for both samples, it can be concluded that the adsorption isotherm models for both are Langmuir and Freundlich. The Langmuir adsorption isotherm is associated with a chemisorption process that occurs through the formation of a monolayer or single layer on the adsorbent's surface, while the Freundlich isotherm is employed to determine the physical adsorption process that occurs on the surface of the adsorbent's heterogeneous active groups [22,23]. After plotting the data from adsorption experiments for both modified and unmodified red mud adsorbent, based on Eqs.…”
Section: Adsorption Isotherm Modelmentioning
confidence: 99%
“…Based on the R 2 for both samples, it can be concluded that the adsorption isotherm models for both are Langmuir and Freundlich. The Langmuir adsorption isotherm is associated with a chemisorption process that occurs through the formation of a monolayer or single layer on the adsorbent's surface, while the Freundlich isotherm is employed to determine the physical adsorption process that occurs on the surface of the adsorbent's heterogeneous active groups [22,23]. After plotting the data from adsorption experiments for both modified and unmodified red mud adsorbent, based on Eqs.…”
Section: Adsorption Isotherm Modelmentioning
confidence: 99%